An Exploratory Electromyography-Based Coactivation Index for the Cervical Spine. (February 2018) - Le, Peter; Aurand, Alexander; Best, Thomas M.; Khan, Safdar N.; Mendel, Ehud; Marras, William S.
Objective: Develop a coactivation index for the neck and test its effectiveness with complex dynamic head motions. Background: Studies describing coactivation for the cervical spine are sparse in the literature. Of those in existence, they were either limited to a priori definitions of agonist/antagonist activity that limited the testing to sagittal and lateral planes or consisted of isometric exertions. Multiplanar movements would allow for a more realistic understanding of naturalistic movements in the cervical spine and propensity for neck pain. However, a gap in the literature exists in which a method to describe coactivation during complex dynamic motions does not exist for the cervical spine. Methods: An electromyography-based coactivation index was developed for the cervical spine based on previously tested methodology used on the lumbar spine without a high-end model and tested using a series of different postures and speeds. Results: Complex motions involving twisting (i.e., flexion and twisting) and higher speed had higher magnitudes of coactivation than uniplanar motions in the sagittal or lateral plane, which was expected. The coupled motion of flexion and twisting showed four to five times higher coactivation than uniplanar (sagittal or lateral) movements. Conclusion: The coactivation index developed accommodates multiplanar, naturalistic movements. Testing of the index showed that motions requiring higher degrees of head control had higher effort due to coactivation, which was expected. Application: Overall, this coactivation index may be utilized to understand the neuromuscular effort of various tasks in the cervical spine.